2014
DOI: 10.1364/ol.39.006743
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chain-transferring thiol functionalities on the performance of nanoparticle-polymer composite volume gratings

Abstract: We report influences of varying functionalities of thiols as chain transfer agents on the spatial frequency response, polymerization shrinkage, and thermal stability of a volume grating recorded in a photopolymerizable ZrO₂ nanoparticle-polymer composite film. It is shown that a substantial increase in the saturated refractive index modulation is realized at high spatial frequencies by doping with multifunctional thiols. Moreover, the incorporation of multifunctional thiols considerably suppresses polymerizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…However, in order to explain various experimental observations (e.g. a strong grating-spacing dependence on [ 35 , 41 , 47 , 71 , 72 , 74 , 76 ]) and to make the material optimization possible for specific applications, one needs to establish a more appropriate statistical thermodynamic model that accurately takes the interaction of nanoparticles with monomer and the formed polymer [ 119 ] into account.…”
Section: Holographic Grating Formation and Grating Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in order to explain various experimental observations (e.g. a strong grating-spacing dependence on [ 35 , 41 , 47 , 71 , 72 , 74 , 76 ]) and to make the material optimization possible for specific applications, one needs to establish a more appropriate statistical thermodynamic model that accurately takes the interaction of nanoparticles with monomer and the formed polymer [ 119 ] into account.…”
Section: Holographic Grating Formation and Grating Characterizationmentioning
confidence: 99%
“…However, the reduced shrinkage of volume gratings recorded in MA-based NPCs was still of the order of 1%, larger than the shrinkage criterion ( 0.5%) for HDS [ 27 ]. This shrinkage problem can be relaxed to some extent by the addition of chain transfer agents by which rapid gelation is delayed and thereby shrinkage can be reduced [ 71 , 72 ]. In order to mitigate shrinkage further, we proposed the use of thiol-ene (TE)/thiol-yne (TY) monomers capable of free radical step growth polymerization in NPCs and showed a substantive reduction in shrinkage as low as 0.4 % without decreasing and S [ 73 77 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has recently been shown that the addition of a chain transfer agent to a NP‐doped formulation results in a remarkable twofold improvement in usable Δ n , to as high as 0.016, without any increase in the nanoparticle loading (or, therefore, any increase in the formula limit). Instead, this improvement is attributed to more favorable reaction/diffusion kinetics, which also result in improved index response at high spatial frequencies …”
Section: Formula Limit Conceptmentioning
confidence: 99%
“…In contrast, polymers offer much larger refractive-index modulations (up to 102 [3]), but are less controllable, e.g., with respect to shrinkage or thermal stability. Over the last two decades, the focus moved to polymer composite materials, such as polymer liquid crystal composites (H-PDLC [4,5,6,7,8,9], POLICRYPS [10,11,12]) or polymer nanoparticle composites [13,14,15,16,17,18,19,20,21,22,23]. Another recently introduced composite consists of ionic liquids embedded in a polymer matrix [24], the material investigated in this study.…”
Section: Introductionmentioning
confidence: 99%